Religion of sports : navigating the trials of life through the games we love - Chopra, Gotham, 1975-; Levin, Joe (Atria Books, an imprint of Simon & Schuster, Inc., 2023)
"From pilgrimages and cathedrals, gods and fallen angels, holy wars and holy ghosts, sports has every aspect of an organized faith. Tracing his unique path from being a diehard fan to witnessing miracles alongside the gods of sport, the author makes a compelling case for sports as a modern-day faith. He presents stories about some of the biggest names in sports. Learn how Tom Brady managed the end of his career, Simone Biles overcame the pressure of the Tokyo Olympics, and Golden State Warriors sharpshooter Stephen Curry developed the greatest three-point shot of all time. Chopra weaves together stories from the likes of Kobe Bryant, Alex Morgan, LeBron James, Michael Strahan, Shaun White into modern-day parables that unlock secrets of competition and life."--Publisher.